Benefit and cost of repeating a severe acute respiratory coronavirus virus 2 (SARS-CoV-2) polymerase chain reaction (PCR) test after the second day of hospitalization in five hospitals during various community prevalences and vaccination rates. (16th June 2022) - Bulnes, Rene; Said, Mina; Bronstein, Melissa; Gutowski, Jennifer; Alag, Karan; Bress, Jonathan; Dellefave, Amber; Riedy, Dawn; Alcantara, Jose; Bhavsar, Hiloni; Gargano, Bryan; Lesho, Emil
Abstract: At our hospital, universal severe acute respiratory coronavirus virus 2 (SARS-CoV-2) polymerase chain reaction (PCR) testing was performed upon admission and again after 2 inpatient days. As community-wide prevalence, admission, and vaccination rates varied, the number needed to benefit fluctuated between 16 and 769 and the cost per additional detection fluctuated between $800 and $29, 400. These 2 metrics were negatively associated with new hospital admissions. No other community indicator was associated with the number needed to benefit and cost per additional detection.